1975
DOI: 10.1210/jcem-41-4-777
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spironolactone on Sex Hormones in Man

Abstract: Administration spironolactone at a dosage of 400 mg/day to healthy male volunteers for 5 days resulted in a significant rise in plasma progesterone and 17alpha-hydroxyprogesterone which persisted throughout the study. A transient increase in plasma FSH and LH concentration was observed after the second but not the third or fifth days of drug administration. There was no change in plasma concentration of testosterone, 17beta-estradiol, or prolactin. These findings are consistent with a previously-reported spiro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
2
1

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(36 citation statements)
references
References 1 publication
2
29
2
1
Order By: Relevance
“…These results differ from those of Stripp et al (1) who observed a 2-fold increase in this steroid in normal human volunteers receiving the drug for 3-5 days. Several differences, however, exist between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results differ from those of Stripp et al (1) who observed a 2-fold increase in this steroid in normal human volunteers receiving the drug for 3-5 days. Several differences, however, exist between the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…A RECENT report (1) indicated that plasma progesterone and 17a-hydroxyprogesterone levels are elevated in spironolactone-treated human subjects and that this effect may be related to a drug-induced adrenal enzyme inhibition. We have recently shown (2) that plasma 11-deoxycorticosterone (DOC) levels measured by a number of radioassay methods are spuriously elevated in spironolactone-treated individuals, and that drug interference in the assay systems was responsible for the high values obtained.…”
mentioning
confidence: 99%
“…The combined treatment with spironolactone and testolactone has been shown to be effective in blockade of androgen action in familial testotoxicosis [11 ]. Spironolactone decreases the activity of microsomal enzyme cytochrome P450 in testosterone synthesis [21] and peripherally by competing with 5c~-dihydrotestosterone for the specific receptor [3]. Testolactone, a competitive inhibitor of the enzyme aromatase, counteracts the persistent oestrogen synthesis induced by spironolactone [11].…”
Section: Discussionmentioning
confidence: 99%
“…auf eine Androgenreduktion im Hin blick auf den Hirsutismus nicht ansprechen und bei denen auch die SHBG- 2. Eine Blockierung der Androgenrezeptoren wird dem Spironolacton zugeschrieben [5]. Während eine diesbezügliche Untersuchung, die Rezep toren vor und nach der Spironolactontherapie vergleicht, noch nicht been det ist, können wir aber andererseits bereits Haarveränderungen an 14 Frauen, die mit Spironolacton behandelt wurden, beobachten.…”
Section: Therapie Und Ergebnisseunclassified